2022
DOI: 10.3390/tropicalmed7120445
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi Parasite Burdens of Several Triatomine Species in Colombia

Abstract: Trypanosoma cruzi, the causal agent of Chagas disease, is mainly transmitted by insects of the Triatominae subfamily. In Colombia, there are 26 triatomine species, and 16 of them are naturally infected with the parasite. The parasite loads of naturally infected vectors can be significant in targeting specific species that can affect the epidemiology of the disease. Studying their ecology and behavior is vital to understand their role in T. cruzi transmission dynamics. We evaluated the parasite loads of 182 fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…cruzi , with Triatoma spp., Rhodnius spp., and Panstrongylus spp. most associated with transmission to people [ 46 ]. For a triatomine species to be efficient for vector-borne transmission of T .…”
Section: Why Does Oral Infection Results In More Severe Symptoms?mentioning
confidence: 99%
“…cruzi , with Triatoma spp., Rhodnius spp., and Panstrongylus spp. most associated with transmission to people [ 46 ]. For a triatomine species to be efficient for vector-borne transmission of T .…”
Section: Why Does Oral Infection Results In More Severe Symptoms?mentioning
confidence: 99%
“…Peridomestic human exposure to triatomine vectors has been increasing in certain regions of Colombia and throughout other regions of Latin America and the United States [ 9 , 94 , 95 , 96 , 97 ]. Invasion from adult insects has been associated with confirmed or suspected cases of oral Chagas disease [ 5 , 14 ].…”
Section: Peridomestic Triatomines Associated With Oral T Cr...mentioning
confidence: 99%
“…During warm weather, both species tend to invade human dwellings. Moreover, recent findings have revealed that both species carry high loads of T. cruzi in their hindguts [ 97 , 100 ]. These simultaneous biological characteristics could elucidate the significance of these species in facilitating oral transmission in Colombia.…”
Section: Peridomestic Triatomines Associated With Oral T Cr...mentioning
confidence: 99%
See 1 more Smart Citation
“…This Special Issue explores the vector’s contribution to disease spread. Velásquez-Ortiz and co-workers [ 11 ] detected high parasite loads in triatomines belonging to 10 species in different regions in Colombia, including species whose role as vectors is still unknown. The results pointed to the possible role of secondary species in T. cruzi transmission and the need to improve vector control programs in the country.…”
mentioning
confidence: 99%